Positif Correlation of Hormonal Contraception and The Occurrence of Leucorrhoea - Mirza Aulia Cahyani; Ira Titisari; Lumastari Ajeng Wijayanti (STIKes Patria Husada Blitar, 2023)
Hormonal contraceptives contain estrogen and progesterone. Prolonged use causes a higher dose of the estrogen and progesterone hormones that can cause leucorrhoea or vaginal discharge. Analyzing and reviewing articles related to the relation between the use of hormonal contraceptive methods with the leucorrhoea occurrence. The literature review method used a systematic mapping study design. Literature sources were obtained from the Google Scholar, Pubmed, and Proquest databases with 6 years of publication. The literature collection strategy using PEOS was then selected to produce 10 articles that matched the research criteria. Of 10 articles that examined the type of hormonal family planning (KB) that were mostly used were 3 articles with injectable KB, 2 articles on pill KB, 2 articles on KB implants, and 3 articles that did not mention the type. There were 3 articles describe that both <1 year and >1 year duration of the usage can cause vaginal discharge. There were 7 articles with analytical tests, 4 articles (57%) stated that there was a relation between the use of hormonal contraceptive methods and the occurrence of vaginal discharge, while 3 articles (43%) stated that there was no relation between the use of hormonal contraceptive methods and the occurrence of vaginal discharge. There were 3 articles that did a descriptive analysis, it was found that contraceptive users who experienced vaginal discharge were more than 35%. The use of hormonal contraception can cause physiological vaginal discharge since the hormones progesterone and estrogen change the flora and pH of the vagina, besides that vaginal discharge occurs because personal hygiene is not correct